Epidemiology of Chikungunya Outbreak at Pelem Village, Boyolali, 2024 - Presenta, Lorda; Adi, Mateus Sakundarno; Suhartono, Suhartono; Kuncoro, Teguh Tri (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: There was no reported case of Chikungunya, during the last five years in Pelem Village, Boyolali, but on September 21, 2024, the Simo Health Center found a suspected case of chikungunya in Pelem Village. This study aimed to describe the chikungunya outbreak in Pelem Village, Boyolali Regency in 2024. Methods: A descriptive observational study was conducted based on epidemiological data according to the characteristics of people, places, and time. Data were collected through active case-finding, interviews using questionnaires, environmental observations, and confirmation cases using a Rapid Diagnostic Test (RDT). Results: A total of 54 cases were identified from June to September and were distributed across four hamlets. To confirm the outbreak, RDT was performed in 11 cases, and seven cases were positive for chikungunya. Common symptoms included fever and joint pain (100.0%), rashes (66.7%), muscle pain (57.4%), headache (42.6%), and nausea (38.9%). The cases mainly occurred in female (51.9%), those aged 27-46 years (37.0%), and those with a medical history (63.0%). Wonokerti hamlets had the highest attack rate (9%). Of the 26 houses observed in the environmental observations, 11 houses were positive for larvae (42.3%) with a container index of 22.2% and a Density Figure indicating the potential for chikungunya transmission. Conclusion: The Chikungunya outbreak in Pelem Village occurred from June to September 2024. The 3M+ method (Burying, Draining, and Recycling) should be implemented to increase mosquito nest eradication and conduct periodic larval monitoring.